1992
DOI: 10.1111/j.1600-0587.1992.tb00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat associations of carabid beetles in fields and forests on the Åland Islands, SW Finland

Abstract: Carabid beetles (Coleoptera, Carabidae) were collected by using pitfall traps in 68 sites on the Åland Islands, SW Finland The sites were divided into four environmental types 1) cultivated fields and grazed pastures. 2) recently abandoned fields, 3) abandoned, overgrown cultivations, and 4) forests A total of 4901 carabids belonging to 77 species were caught Twenty of the most abundant species were classified into four distributional types according to their occurrence among the various environmental types 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 20 publications
4
33
0
1
Order By: Relevance
“…The greater geographical separation of sites in the present study (up to approximately 13 km compared to only 1.5 km with Catteral et al (2001)) is probably also a factor in the greater community turnover between sites. Site differences possibly relate to factors including the intrinsic patchiness of beetle occurrence (Niemelä et al 1986;Niemelä et al 1992), the geographical separation of sites and species turnover (Gering et al 2003;Summerville et al 2003), possible differences in fire history (frequency, intensity) and stand characteristics, a different soil type and a microclimate influenced by a waterfall in the case of the Isabel Creek site, and a 250 m elevation range. The beetle assemblage at the sedimentary Isabel Creek site fell within the range of assemblages at the three dolerite-derived sites (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The greater geographical separation of sites in the present study (up to approximately 13 km compared to only 1.5 km with Catteral et al (2001)) is probably also a factor in the greater community turnover between sites. Site differences possibly relate to factors including the intrinsic patchiness of beetle occurrence (Niemelä et al 1986;Niemelä et al 1992), the geographical separation of sites and species turnover (Gering et al 2003;Summerville et al 2003), possible differences in fire history (frequency, intensity) and stand characteristics, a different soil type and a microclimate influenced by a waterfall in the case of the Isabel Creek site, and a 250 m elevation range. The beetle assemblage at the sedimentary Isabel Creek site fell within the range of assemblages at the three dolerite-derived sites (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…However, relatively few published studies have been devoted to the carabid fauna of old-field successions. Comprehensive work on diversity and species richness of carabids in successions on abandoned fields have been carried out in Germany (e.g., Klinge 1993), the USA (e.g., Siemann et al 1999, who considered the entire arthropod fauna), and related studies on carabids are reported from e.g., Finland (Niemela and Halme 1992), Belgium (Desender and Bosmans 1998), and Japan (Yamazaki et al 2003). When 2, 4, and 20 year old fallows in northern Germany were compared (Klinge 1993) the highest species richness was recorded in the youngest sites and larval hibernating species decreased with increasing age of the sites.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies demonstrated that carabid species can be classified according to their spatial pattern into habitat generalists, forest generalists, forest specialists and species of open habitats (de Warnaffe and Lebrun, 2004;Niemelä and Halme, 1992;Magura et al, 2000). In this study species characterising a habitat type were found only in sites with native trees in the canopy: atlantic mixed forest, beech forest and mixed pine plantations (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…Moreover distribution patterns and composition seem to be related to habitat heterogeneity at various spatial scales (Niemelä and Halme, 1992;Penev, 1996). Our study however presents very different results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation